Sokrates a etyka biznesu (Rozważania o etycznych źródłach odpowiedzialności) - Podrez, Ewa (Annales. Etyka w Życiu Gospodarczym, 2008)
The presented work attempts to show a link between business and global responsibility with the Socratic idea of self-knowledge. The today’s ethics discusses the fundamental issues of the man’s place in the world. The human existence is one of the causes of the contemporary crisis. This crisis between man and the world obliges us to raise a radical question of the ethical origins of individual and global responsibility for the quality of life, including also the future human generations. This question requires going back to the historical and ethical considerations about the Socratic project of good life. The starting point for the Socratic ethics is an interpersonal and inner-personal dialogue; the subsequent result of that is man’s practical wisdom of how to build his own life together with others. Socrates argues that the key issue of responsibility is awakening of self-awareness and the way to achieve this objective is dialogue.